A Novel Grid-Forming Strategy for Voltage-Source Controlled PV Under Nearly 100% Renewable Electricity - Hu, Pan; Jiang, Kezhen; Ji, Xiaotong; Tan, Daojun; Liu, Dan; Cao, Kan; Wang, Wei (Frontiers in Energy Research, 2022)
The demand for decarbonization calls for nearly 100% renewable electricity (RE) rising as the dominant power resources. The foregoing paradigm shifts require proactive voltage and frequency controller for the converter-based renewable energy. This paper proposes a novel grid-forming technique for voltage-source controlled photovoltaic (PV) operating in 100% renewable power systems. The proposed idea is to design a DC voltage collapse-prevention controller in conjunction with a simplified frequency and inertia controller thereby smart capturing and releasing PV energy to achieve improvements in dynamic performance and efficiency. With setting the two-phases operation scheme, the model initiatively considers the conflict between frequency regulation and Maximum Power Point Tracking (MPPT) curve control. The preferred controls are validated using extensive simulation and experimental findings based on a semi-physical platform and a practical photovoltaic demonstration project. The proposed controller outperforms the standard PV current controller over a much larger range of weak grid situations, according to the experimental and engineering operational data. Results demonstrate the effectiveness of the presented method in applying to the future 100% renewable power system.